Optimization of parameters affecting hexavalent chromium biosorption using cinetobacter haemolyticus and Eschericia coli - Siti Khairunnisa Yahya, 1986-; Wan Azlina Ahmad, supervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2008